50‐4: Optical Design of Corner‐Cube Retroreflectors with Inclined Curved Optical Surfaces for Directional Scattering Projector Screen. Issue 1 (28th June 2021) - Käläntär, K.; Uchida, T.
Abstract : An array of hollow corner cube retroreflectors (CCR) with inclined and curved optical surfaces has been designed to realize a directional scattering projector screen. The characteristics of our previously reported projector screen were further modified by emphasizing on the design accuracy and precision of the screen unit cell. The rhombus screen unit cell which is a combination of two directional scattering CCRs with equilateral triangle apertures set back to back, was modified to increase the scattering light. The source of optical noise on the screen and the result of modification are reported.